HUBUNGAN KARAKTERISTIK IBU NIFAS TERHADAP PEMILIHAN METODE KONTRASEPSI PASCASALIN DI PUSKESMAS SELOPAMPANG KABUPATEN TEMANGGUNG - Sumarsih, Sumarsih (Sinar : Jurnal Kebidanan, 2023)
Objective: The goals and benefits of family planning are to slow population growth , regulate spacing and delay pregnancy , reduce infant mortality , empower communities and improve education , and reduce teenage pregnancies ( young ages ). Postpartum mothers in their 42 days are very important to use family planning , but there are still many who still feel afraid , indecisive and unsure about doing family planning . especially postpartum family planning , especially for IUD acceptor users . Meanwhile , for injections , respondents also feel afraid of drastic weight gain . For pills , you must always remember every day . This study aimed to determine the relationship between the characteristics of postpartum mothers and the choice of their contraceptive methodsMethods: This research was an observational analytic study using cross sectional approach . The sampling technique used was a saturated sample with a whole population of 60 postpartum women in their 42 days as respondentsResults: The results of the study revealed that there was no relationship between the characteristics of the postpartum mothers and the choice of postpartum contraceptive methods. The statistical test used was the chi - square test . Based on the results of the analytical test using the Chi - square test , it was known that p - 0.179 was greater than p - value < 0.05 so that it could be concluded that there was no relationship between the characteristics of the postpartum mother's work and the choice of their contraceptive methodsConclusion: There was no relationship between the characteristics of the postpartum mother's work and the choice of their contraceptive methods . Midwives need to improve education or motivation for postpartum mothers regarding the importance of using family planningÂ